CLASSES ABSTRATAS UM ESTUDO DE CASO APLICADO AO SISTEMA DE INFORMAÇÃO DE GESTÃO UNIVERSITÁRIA - Silva, Filipe D. d.; Silva, Jaime R. d.; Weber, Juliano G.; Boniati, Bruno B. (Salão do Conhecimento, 2013)
Resumo